Friedel–crafts alkylation over Zr-mont catalyst for the production of diesel fuel precursors - Shinde, Suhas; Rode, Chandrashekhar Vasant (ACS Omega, 2018)
Heterogeneous Zr-Mont catalyst prepared by a simple protocol was employed for the production of diesel fuel precursors via Friedel–Crafts (FC) alkylation of petroleum-derived arenes (e.g., mesitylene, xylene, and toluene) with biomass-derived 5-(hydroxymethyl)furfural (HMF), HMF derivatives, and carbohydrates. Initially, several acidic catalysts were screened for the FC alkylation of mesitylene with HMF in nitroethane solvent. Among all, Zr-Mont catalyst gave an exceptionally high yield (80%) of mesitylmethylfurfural (MMF). The catalytic activity of Zr-Mont was also evaluated for the alkylation of different petroleum-derived arenes with ester/halogen derivatives of HMF. Suitable acid strength and high surface area of Zr-Mont were its major attributes to make it the most efficient solid acid catalyst for this FC reaction. Even after several reuses, the catalytic activity of Zr-Mont was found to be consistent, which was also evidenced by the acidity measurements of fresh and reused Zr-Mont catalysts by temperature-programmed desorption of ammonia and pyridine Fourier transform infrared spectroscopy techniques. Direct conversion of glucose to diesel fuel precursors was also attempted over Zr-Mont catalyst in mesitylene and polar nonacidic solvents at 150 °C. However, the activity of Zr-Mont catalyst was limited for glucose dehydration to HMF and MMF did not form. When the same experiment was performed in formic acid medium, MMF was produced in 34% yield. After the addition of formic acid, the reaction becomes biphasic which contains mesitylene as an organic phase and formic acid as an aqueous phase. Formic acid worked as a solvent, reactant, and cocatalyst, whereas mesitylene worked as a reactant and product extraction phase to enable easy product isolation. With this strategy, other diesel fuel precursors were also produced in 26–30% yields from glucose and different arenes. Similar strategy was successfully extended for the conversion of sucrose to diesel fuel precursors.